“Lingo Climb” for vocabulary learning: Developing a game-based learning tool for elementary EFL students - Sofiana, Nina; Putri, Aprilia Riyana; Muzakki, Muhammad Alie; Mubarok, Husni (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Vocabulary acquisition is essential for language learning, yet many students in English as foreign language (EFL) contexts struggle with traditional, rote-based instruction that lacks engagement and contextual relevance. This study addresses this gap by developing and evaluating “Lingo Climb”, a game-based vocabulary learning tool inspired by the Snake and Ladder game, tailored for Indonesian elementary school students. Employing the ADDIE model, the study progressed through needs analysis, product development, and evaluation phases. A mixed-method approach was used, incorporating surveys, interviews, observations, and pre and post-tests during small-scale trials involving 24 students and two teachers. Results indicated significant improvements in students’ vocabulary mastery, with teachers and students praising the tool for its cultural relevance, practicality, and ability to foster engagement and collaboration. The findings highlight the potential of